Studi Deskriptif Pengelolaan Sampah di Sekolah Dasar Negeri 07 Kota Bengkulu - Oktriasih, Dian Roshella; Lusa, Herman; Tarmizi, Pebrian (JURIDIKDAS, 2024)
This research was aimed to describe the trash management at the State elementary School 07 Bengkulu City focusing on the primary school’s trash management. This was a qualitative research with a descriptive method. The subjects of this research were the head master, teachers and students. The data gathering techniques used were observation, interview, and documentation. The data were analyzed by checking the result of the observation, interview and documentation to further being analyzed into the data reduction, data presentation, and data conclusion. The credibility checking was done by doing the double checking, using the triangulation, and conducting the member checking.The results of this research showed that the trash management planning was programmed in the vision, mission, values of the organization, strategic environmental analysis, key indicators of the successfulness, goals and targets, and strategies (program and activities). This plan was made systematically as the base for State Elementary School 07 Bengkulu City’s trash management resulted into a coherent, synchronized, and solid program.